OP08 Evidence for early astrocyte activation, cellular stress and compensatory microglial related transforming growth factor-α responses in bile-duct ligated rats. (16th November 2010) - Wright, G; Wright, G; Newman, T; Sharifi, Y; Davis, N; Jalan, R
Abstract : Introduction: Inflammation and ammonia are important mediators in the pathogenesis of hepatic encephalopathy and though the mechanisms are unclear astrocytes are thought to have a central role. Recently Microglia, which also mediate brain inflammation, were implicated in the brain effects of acute liver failure; however their influence in chronic liver disease is unknown. Aim: The aim of this longitudinal study was to characterise the early brain responses in bile-duct ligated (BDL) rats in the 4-weeks following ligation. Method: Twenty-four male Sprague-Dawley rats were studied after sham-operation or BDL and sacrificed at either 1-day or, 1-, 2- or 4 weeks post-surgery (n=4/group). Consciousness, brain water content, arterial ammonia, plasma biochemistry and proinflammatory (IL-6, TNF-α and γ-IFN) and antiinflammatory (IL-4 and IL-10) cytokines, were analysed. Immunohistochemical markers of activated microglia (ED1, OX6 and Iba-1), astrocytes (GFAP), inflammatory responses (IL-1ß and iNOS), cellular stress (HSP-25) and the predominant antiinflammatory and alternative microglial activation marker TGF-ß (using RT-PCR), were also analysed. Results: Compared to Shams, arterial and brain ammonia (p<0.001, respectively), bilirubin (from day-1) and the cytokines, TNF-a and IL-6 were significantly increased by 4 weeks BDL (p<0.001), which induced mild brain oedema (p=0.07). There was no evidence of classical microglial activation or cellular infiltration (indicated by negative OX6 staining and few perivascular ED1 positive cells evident in all groups), with observable resting microglia (Iba-1 positive staining) in all groups. Protein expression for iNOS and IL-1ß increased using Western blotting. Increased GFAP staining indicated significant astrocyte activation, primarily in the corpus callosum in all BDL groups. Hsp 25 (cellular stress indicator) peaked at 2 weeks post-BDL and was located mostly in the corpus callosum similar to activated astrocytes. TGF-ß was significantly upregulated by 3-fold in all BDL groups. Conclusion: Regional astrocyte activation and cellular stress (indicated by increased HSP-25 expression), are early features of BDL. These events are associated with increased brain proinflammatory cytokine production and iNOS expression. This proinflammatory response is not due to obvious microglia activation, but consequent upon activation of astrocytes, possibly related to hyperammonemia and/or associated cell swelling. However, an observed TGF-ß response may reflect compensatory antiinflammatory microglial responses, designed to limit the effect of astrocyte activation; with interventions targeting its brain expression potential novel therapies for hepatic encephalopathy.